Information and communication technologies for development and poverty reduction: The potential of telecommunications - Torero, Maximo; von Braun, Joachim (International Food Policy Research Institute, 2006)
The variety of views about ICTs reveals that their role in development is unclear, especially without convincing evidence of their impact—and little research has been conducted on the direct and indirect links between ICTs and poverty reduction. This book, addresses several pressing questions surrounding ICTs. How do ICTs affect economic development in low-income countries? How do they affect poor people in these countries and in rural areas in particular? What policies and programs facilitate their potential to enhance development and the inclusion of poor constituents?